Her unforgettable knight - Oliver, Melissa (Harlequin historicals., 2023)
Marguerite never expected to see Savaric again--let alone to have to help him when she finds him outnumbered in a fight. He's the brooding knight she fell for two years ago...until he left her unexpectedly. Now Marguerite is a hardened spy and wary of trusting him again. But how long can she resist their connection when they must work together to protect the Crown?